Revealing the reality and solutions to domestic violence - Hasudungan Sinaga (IHSA Institute, 2023)
Family is the main foundation of society. Every family carries the dream of building a harmonious, loving and happy environment. A healthy family is the foundation for the growth and development of individual family members, as well as their positive contributions to society at large. However, behind this dream, there is a reality that illustrates how complex family dynamics are in facing challenges that come in the form of domestic violence. Therefore, handling domestic violence cannot only rely on a legal approach alone, but also requires a change in people's mindset and awareness of domestic violence. Research is expected to inform strategies to provide better protection for victims of domestic violence and alleviate the situation of domestic violence. Research is expected to inform strategies to provide better protection for victims of domestic violence and alleviate the situation of domestic violence. Future research is expected to conduct in-depth analysis of factors that increase the risk of domestic violence as well as factors that can protect individuals from violence.